IoT based drainage monitoring system - Venoth, Abhinaashgovin; Sankaran, Sukhiirtan; Velan, Sheshan; Moganthera Thevar, Atishvar; Saravanan, Sharvin (Universiti Teknologi MARA, Kedah, 2023)
The IoT drainage monitoring system is an innovative solution that utilizes Internet of Things (IoT) technology to address drainage blockages in urban areas. By deploying sensors and devices within the drainage infrastructure, the system continuously collects data on water flow rates, levels, and quality. This real-time data is wirelessly transmitted to a central monitoring system, where it is analysed using advanced algorithms. The system enables early detection of blockages and abnormal patterns, triggering immediate alerts for timely intervention. By proactively identifying issues, the system minimizes the risk of backups, overflows, and flooding. Additionally, it provides insights for proactive maintenance planning, optimizing resource allocation and improving overall drainage system efficiency. The IoT drainage monitoring system enhances the resilience and reliability of urban drainage systems, ensuring public health, safety, and environmental protection while offering cost savings through reduced reactive maintenance and minimized damages.